Sexual Violence and Gendered Policy Responses in an Indonesian Urban Governance: A Critical Feminist Perspective - Alfiana, Alfiana (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
This study provides a critical feminist analysis of how women’s roles in social production and reproduction, coupled with inadequate government policies, shape their vulnerability to sexual violence in Makassar City. Employing a qualitative descriptive methodology, the research draws on data from observations, in-depth interviews, and documents collected from a diverse range of sources including government bodies, women’s organizations, legal aid institutions, and labour unions. The participants encompassed white-collar and blue-collar women workers, housewives, and domestic workers. Through Nancy Fraser’s critical feminist framework, the study indicates that the capitalist system imposes a double burden on women, exploiting their labour in the workplace through wage discrimination and limited career progression while simultaneously relying on their unpaid, devalued domestic and care work within the household. The dynamic fosters economic dependence on husbands and subordination in decision-making, intensifying their vulnerability. The study further concludes that existing government policies are ineffective in safeguarding women’s basic rights, offering weak protections and social assistance. Consequently, this research offers a significant critique of the modern capitalist system’s exploitation of women across both productive and reproductive spheres. Its value lies in providing empirically grounded recommendations for formulating more responsive, progressive policies to protect female workers and housewives, and for reforming legal and institutional guidelines for handling sexual violence cases, thereby contributing to both academic discourse and practical policy reform.